Implementasi Etika Bisnis Islam Dalam Budidaya Udang Vaname - Mastura, Mastura (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Cultivating vaname shrimp, pond farmers are required to act in accordance with Islamic business ethics. Pond farmers are required to act without deliberate contradictions between words and actions in their business. Pond farmers must have the principles of Unity (tauhid), Balance (justice), Responsibility, Truth (virtue and honesty) and free will (Ikhtiyar), that there are several problems that occur in vaname shrimp cultivation activities. Among them is the provision of pesticides so that they can kill other animals. This research aims to find out how Islamic business ethics are implemented in vaname shrimp cultivation activities. The research approach used is a qualitative approach. The nature of this research is descriptive-analytical research. Data collection techniques in this research used literature, documentation and interviews. Data analysis techniques are carried out using inductive thinking. The results of the research show that the implementation of Islamic business ethics in vaname shrimp cultivation activities in West Langsa subdistrict, Aceh Province has implemented Islamic business ethics in the principles of Unity (tauhid), Balance (justice), Responsibility, Truth (virtue and honesty). Meanwhile, regarding the Islamic business ethics principle of free will (Ikhtiyar), pond farmers have not been able to apply it, they still use pesticides in the initial process of eliminating pests such as snakes, small fish, small crabs, and this can damage the environment. and cause harm to other animals. This research provides deeper insight into Islamic business ethics in terms of vaname shrimp cultivation.